Principles of Designing Commercial Buildings in Historical Cities of Uzbekistan (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article is devoted to a comprehensive study of the principles of designing commercial buildings in the historical cities of Uzbekistan. We analyze in detail the main problems that arise along the way, propose effective solutions based on world best practices, and draw on the opinions of leading international experts in the field of architecture and urban planning.